Halal Certification in The Digital Age: Leveraging Online Platforms for Enhanced Transparency and Accessibility - Nusran, Muhammad; Nasution, Evriza Noverda; Prayitno, Mustofa Aji; Sudarmanto, Eko (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2023)
This article discusses the role of digital technology in halal certification in the digital era. The research aims to understand the impact of digital technology on halal certification and its global implications. The research method used is literature analysis, which helps researchers formulate a comprehensive understanding of this topic. In the literature analysis, researchers explore the history of halal certification, the development of digital technology in the context of halal certification, and its impact on transparency and accessibility. Additionally, researchers also consider the challenges and ethical considerations that arise with the use of digital technology in halal certification. The article also discusses the role of the Internet of Things (IoT), Artificial Intelligence (AI), and blockchain technology in enhancing halal certification. IoT enables real-time monitoring in the supply chain, while AI supports in-depth data analysis. Blockchain technology provides integrity and transparency in certification. Mobile applications also create greater accessibility for consumers to check the halal status of products. The research findings indicate that digital halal certification has a significant global impact, not only meeting the needs of Muslim consumers but also gaining recognition from non-Muslim communities. Despite challenges such as data security and ethical considerations, the use of digital technology in halal certification opens the door to the growth of a more inclusive, transparent, and halal-compliant food and beverage industry.